Moving Asset Tracking Using GPS Sensor and Internet of Things - Suakanto, Sinung; Nugroho, Tunggul Arief; Nuryanto, Edi; Lathifah, Syfa Nur; Nuraliza, Hilda (Jurnal Telematika, 2024)
Moving assets, such as buses, trucks, and trains, are important productive assets, especially in the transport industry. Effective tracking of these assets is essential to optimize operations, ensure safety, and minimize costs. However, traditional tracking methods often lack real-time monitoring, which leads to inefficiencies and potential risks. This research proposes a mobile asset tracking system with a special focus on railway assets and leverages GPS technology for real-time positioning and IoT for data transmission to a cloud-based data center. A prototype of the system was successfully developed using hardware connected to a GPS device that continuously transmits location data. In this paper, an application for visualization management has also been developed to display asset data and track asset positions in real time. Performance evaluation was conducted using the RAMS (reliability, availability, maintainability, and safety) framework, which showed an average update interval of 49 seconds, a system availability rate of 94% for one month, and better maintainability due to the plug-and-play nature of the GPS-based system. Although long-term safety improvements require further study, the proposed system improves on existing navigation methods by providing real-time tracking and increasing operator awareness. These findings highlight the potential of GPS and IoT integration in improving asset tracking and operational efficiency in the transport sector.